The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3402/gha.v9.29417
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Integrated Management of Childhood Illnesses strategy: challenges and recommendations in Botswana

Abstract: BackgroundUnder-five mortality has been a major public health challenge from time immemorial. In response to this challenge, the World Health Organization and the United Nations Children's Fund developed the Integrated Management of Childhood Illnesses (IMCI) strategy and presented it to the whole world as a key approach to reduce child morbidity and mortality. Botswana started to implement the IMCI strategy in 1998. Reductions in the under-five mortality rate (U5MR) have been documented, although the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 3 publications
3
20
1
4
Order By: Relevance
“…Other studies further concur with our findings regarding demotivated staff, gaps in training and fragmented communication and supervision from central authorities [ 10 , 22 , 24 , 25 , 38 41 ]. Consistent with our findings, HCWs in several settings feel especially frustrated with the manner in which IMCI leads to an appearance of lower monthly patient counts (due to IMCI’s alternative recording modalities) [ 24 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other studies further concur with our findings regarding demotivated staff, gaps in training and fragmented communication and supervision from central authorities [ 10 , 22 , 24 , 25 , 38 41 ]. Consistent with our findings, HCWs in several settings feel especially frustrated with the manner in which IMCI leads to an appearance of lower monthly patient counts (due to IMCI’s alternative recording modalities) [ 24 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Globally, several vertical child health programs have emerged without clear harmonization to IMCI, which challenges those trying to prioritize across programs at the frontlines of implementation [ 24 , 41 , 45 ]. The manner in which HCWs try to reduce time-consuming administration processes [ 23 , 25 , 36 , 41 , 44 , 46 ], or forgo important IMCI components such as nutritional assessments and counseling tasks is echoed elsewhere [ 24 , 47 – 50 ]. On the other hand, studies from global survey reports have linked demotivation to low salaries [ 20 , 22 ] and job insecurities [ 51 ], which did not emerge in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study from Egypt found a marked acceleration in the annual reduction of under-five mortality after the introduction of IMCI into the national health system [ 63 ]. Other factors include the lack of sufficient numbers of health workers, lack of IMCI-trained staff, high staff turnover, lack of political support and sufficient investment in the health system, and poor implementation of the community component of IMCI in most LMICs [ 5 , 7 , 18 , 34 , 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…After implementation of the Integrated Management of Childhood Illness strategy, there were reductions in the mortality rate, but the figures are still not in line with the expected predictions. Therefore, it is recommended the recognition of clinical conditions during illness, in order to guarantee the reduction of incidence and/or increase of severity in this age group in the emergency services (12) . Despite the prevalence of children with adequate weight for age, the findings showed that the children with high weight for age had a clinical profile of greater severity, in the colors orange and yellow, in relation to the children with low weight (yellow to blue), a finding characterized in the literature as a public health problem that is growing all over the world, since weight gain plays a central role in metabolic changes in childhood, because it predisposes risk factors for cardiovascular diseases (obesity, dyslipidemia, hypertension and glycemia altered), for which the literature suggests the implementation of interventions, through the promotion of healthy eating habits from childhood (12)(13) .…”
Section: Discussionmentioning
confidence: 99%